Concepções e práticas avaliativas nos cursos de licenciatura - Pacheco, Márcia Maria Dias Reis (2008)
The present work aimed at investigating the docents evaluative conceptions at a higher learning institution located in São Paulo state. The research was held with docents actuating in the following areas: Mathematics, Chemistry, Physics, Physical Education, Biological Sciences and Pedagogy, and it was assumed that their evaluative practices would positively influence the students future performance on such pedagogical aspect. The instruments for data collection consisted on a questionnaire and further interviews. It was a questionnaire with closed questions, in a total of 25, based on statements registered on other researches on evaluation applied to the docents of the institution. The answers in the questionnaires were used to elect the docents to be interviewed. The open-ended interviews with the six elected allowed the expression of profound thoughts on the issues investigated: 1. Why evaluating? 2. What is to be evaluated? 3. How to evaluate? The answers were then submitted to the analysis of contents. The theoretical references were concentrated the authors: Luckesi, Prado de Souza, Perreunoud, Hadji and Afonso Janela. It was evidenced that the practices developed by the interviewed has a formative role, being used to detect the students difficulties, raising information and enhancing the educational process. It was also possible to identify that they apply diverse evaluative instruments and procedures, aiming at integrating the evaluative and the teaching-learning processes. The results suggest that the didacticadministrative organization in the institution favors the development of differentiated evaluative practices. This study represented a means to reflect more about the evaluative procedures to be used by future professors actuating within the elementary education, constructing or not differentiated and proficient practices